Hölderlin as Reader of Poetry: Notes on the “Wechsel der Töne” - Ronzheimer, Elisa (Aesthetica Preprint, 2021)
Hölderlin’s fragmentary and enigmatic remarks on the ‘Variation of Tones’ in poetry (‘Wechsel der Töne’) which outline a systematic genre poetics have often been understood as the underlying principle that informed his own poetic production. This paper proposes to conceive of the ‘Variation of Tones’ not as a comprehensive poetics at the basis of Hölderlin’s oeuvre but instead as an instance of his practice of reading. With its particular attention to moments of transition between genres within the poetic text, the ‘Variation of Tones’ emerges as a tool for reading literature defined by genre hybridity. At the same time, it sheds light on Hölderlin’s relational conception of genre poetics which recasts literary genre as a temporary constellation of ‘generic tones’.